INVENTOS Y PATENTES EN LA UNMSM. REFLEXIONES EN UN MARCO DE ACREDITACIÓN UNIVERSITARIA SOBRE EL DOCENTE-INVESTIGADOR, CREADOR E INNOVADOR - Armas Morales, Carlos (2006)
The current article tries to put in agenda the role of researchers and University around inventions and patents as product of researching of the teacher-researchers of Universidad Nacional Mayor de San Marcos (UNMSM), trying to convalidate a set of relationships of equity where benefits and compensations will be levered up, that have to be sustained in a properly labor system from researchers that guarantee and satisfies, in one hand, the role of them with a correct distribution, and in the other hand, the continuity and accredittation of the UNMSM as a contribuitor to the country development in the line of inventions and patents.